PINTAKASI: A UNIFYING FACTOR IN A LOCAL VILLAGE IN THE PHILLIPINES - Bautista, Dennis M.; Abanilla, Charles S.; Matillano, Ariel E.; Abiera, Allan M. (International Journal of Research -GRANTHAALAYAH, 2017)
This is a case study conducted in one of the rural barangays of Leyte. Anchored on the theory of collective effervescence, this study delved into an understanding of a long ago practiced tradition that still thrives even in present times. In synergy, these rural folks enthusiastically come together to solve a problem of any member of the community. Thus, this study has two major concerns: first is to investigate how and why the “pintakasi or bayanihan” spirit of the past still evident today; and second, to rediscover which aspect of the “pintakasi or bayanihan” spirit and the ancient Filipino value hold true in contemporary times. Such queries were answered using a qualitative research approach specifically the ethnographic method in gathering data coupled with a face-to-face interview with ten (10) respondents who were the community officials and elders of this said barangay to discover their social activities and values. As revealed in this study, the rural folks continuously observed the practice because it is innate to them to help especially those in need.